Weak approximations of Wright-Fisher equation - Gabrielė Mongirdaitė; Vigirdas Mackevičius (Lietuvos Matematikos Rinkinys, 2021)
We construct weak approximations of the Wright-Fisher model and illustrate their accuracy by simulation examples.